2017
DOI: 10.1111/php.12801
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Model for Fibroblast Photoaging Comparing Single and Repeated UVA Irradiations

Abstract: The current method for efficient evaluation of antiphotoaging compounds is an in vitro skin culture model using a single ultraviolet A (UVA) irradiation of fibroblasts. However, skin photoaging is caused by repeated exposure to UVA radiation. The objective of this study was to develop an appropriate model for in vitro skin photoaging by comparing the different effects of single (5 J cm ) and repeated exposures (5 J cm × 3 times) of fibroblasts to UVA irradiation. Our results demonstrated that a single and repe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 54 publications
1
22
0
Order By: Relevance
“…We compared the expression of a-SMA in UVA-irradiated cells to non-UVA-irradiated cells. In monolayer, we confirmed the data of our previous study and showed that a-SMA expression does not change (25). In tense collagen lattice, we demonstrated that a-SMA expression in UVA-irradiated cells is lower than in non-UVA-irradiated cell.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We compared the expression of a-SMA in UVA-irradiated cells to non-UVA-irradiated cells. In monolayer, we confirmed the data of our previous study and showed that a-SMA expression does not change (25). In tense collagen lattice, we demonstrated that a-SMA expression in UVA-irradiated cells is lower than in non-UVA-irradiated cell.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, we reported effects of UVA radiation, and no difference of cell number in G2 phase was observed between irradiated and nonirradiated cultures, for both 2D and 3D models. In our previous work, repeated exposure to UVA (5 J cm À2 9 3 times) induced a decline in G2 phase cell number coupled with a damaged cell morphology (a smaller area of cytoplasm) (25). The discrepancy may result from the difference of cell culture conditions.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Only 5% of solar radiation reaches the Earth's surface, comprising wavelengths in the ranges of 315-400 nm (ultraviolet A (UVA)), 280-315 nm (UVB), 100-280 nm (UVC). Specifically, UVA accounts for approximately 96.5% of the daily UV irradiation [1,2]. UVA irradiation can penetrate the epidermal and dermal layers of the skin, and contribute to oxidative stress, premature skin aging, and photo-carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…MMP-1 and MMP-3 are mainly secreted by HDFs, and degrade fibrillary collagen and type IV collagen. Studies on skin photoaging have shown that UVA promotes the degradation of ECM, as evidenced by a reduction in soluble collagen in the dermis that is associated with the upregulation of MMP-1 and MMP-3 [1,9].…”
Section: Introductionmentioning
confidence: 99%